Scaphoid nonunions in skeletally immature adolescents. (July 2014) - Behr, B.; Heffinger, C.; Hirche, C.; Daigeler, A.; Lehnhardt, M.; Bickert, B.
Scaphoid nonunions in children requiring operative treatment are rare. The aim of this study was to analyze our own patient population of the last 13 years to assess the postoperative outcome of these operations. Seven patients, under aged 14 years, were treated for scaphoid nonunions. Patients were clinically and radiologically examined and subjective outcomes were measured, such as the visual analogue pain scale (VAPS), Disability of the Arm, Shoulder and Hand (DASH) score, and Krimmer score. All patients showed an excellent outcome, as determined by the DASH score, Krimmer score, and VAPS. No differences between grip strength and range of motion between the operated and non-operated hand were observed. Therefore, we propose that scaphoid nonunions in skeletally immature adolescents can be treated satisfactorily with excision of the nonunion and bone grafting.